Estudio de prefactibilidad para la instalación de una cadena de cafeterías automatizadas utilizando la domótica - Miñano Martinez, Aldo Fabrizio (2022)
This research proposes the installation of a chain of automated coffee shops using home automation, offering this service in a comfortable place, through a new shopping experience, streamlining the processes using automated machines. The market analysis will take into consideration people between 15 and 49 years belonging to socioeconomic level A and B, residents of Metropolitan Lima, specifically Zone 6 and 7 of the capital, where approximately 78% of our target market resides. The project will start with three stores, located at shopping centers Jockey Plaza, Real Plaza Salaverry and Plaza San Miguel. This is because of our high target market affluence in this establishments, as well as safety compared to street stores. The installed capacity in the production area, thanks to the technology, is greater than the size of the market and the breakeven point, with the size of the market being the limiting factor for the project. The technical specifications of the machinery and equipment, as well as the design of the flow of attention, production and work are detailed and meeting the best standards of technology and customer experience. Likewise, this is accompanied by the hand of an integrated quality management plan, modeling international quality standards, safety assurance, safety, and health at work and environmental management, as well as the 5’s methodology is applied to guarantee the best worker’s productivity. Each establishment will have 130 square meters of area. The company will be of type S.A.C. and the MYPE tax regime will be accepted. The economic and financial viability of the project was determined with an investment of S/ 976,567 distributed in 60% shareholder capital and 40% loan with the BCP bank to a TEA of 15%. The opportunity cost of shareholders is 20.87%. The NPV, IRR, the Profit/Cost ratio and the economic recovery period were S/ 283,564.30, 30.32%, 1.29 and 4.24 years respectively. On the other hand, the financial results were NPV S/ 373,596.47, IRR 38.27%, Profit/Cost ratio 1.64 and recovery period of 3.87 years. A sensitivity analysis was carried out modifying the demand and price variables, being equally viable in all aspects. Finally, the social indicators of employability and capital performance indicate that the project is socially profitable because it contributes to the economic, labor and social growth of the country.